Oxidation of lignocellulosic platform molecules to value-added chemicals using heterogeneous catalytic technologies - Arias, Pedro Luis; Cecilia-Buenestado, Juan Antonio; Gandarias, Iñaki; Iglesias, José; López Granados, Manuel; Mariscal, Rafael; Morales, Gabriel; Moreno-Tost, Ramón; Maireles-Torres, Pedro Jesús (The Royal Society of Chemistry, 2020)
Currently, much attention is being paid to the development of sustainable catalytic processes for the production of chemicals (biofuels, bioproducts, and so on) from lignocellulosic biomass. This minireview pursues to give an exhaustive overview about the heterogeneous catalytic technologies proposed for the oxidation of four key platform molecules (glucose, 5-hydroxymethylfurfural, furfural and levulinic acid) into important chemicals, such as gluconic acid and gluconates, glucaric and formic acids, 2-diformylfuran, 2,5-furandicarboxylic acid, maleic acid and anhydride, succinic acid, furanones, furoic acid, alkyl furoates, furan-2-acrolein, succinic acid, butanone and 3-hydroxypropanoic acid. The different mechanistic pathways will be highlighted, as well as the requirements in terms of catalytic sites and catalyst stability. The challenges and opportunities will be put forward for each type of oxidation process.
Keywords: Energía de biomasa; Catálisis; Lignocellulosic biomass; Oxidation; Heterogeneous catalysis; Platform molecules; Biorefinery